Die terugkeer van die paradys en skepping. Oor nuwe aandag vir Joods-Christelike interpretasies van die paradys-motief - De Villiers, Pieter (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
The return of paradise and creation. On recent attention for Jewish-Christian interpretations of the paradise motif This article investigates several aspects of the renewed interest in paradise in recent research. It outlines the growing lack of interest, especially since the Enlightenment in the motif of paradise. It provides reasons for the renewed interest in it in recent reseach and it then lists some complex results of this research. It discusses biblical material on paradise before it investigates in more detail three foundational aspects of paradise. These include paradise as a spatial reality and as crucial moment in the history of the divine act of salvation. It ends with a discussion of the salvific understanding of paradise.